Uncovering the Link Between Pre-Surgery Constipation and the Success of Surgery for Chronic Anal Fissure - Kudaş, İlyas; Başak, Fatih; Acar, Aylin; Tosun, Hüsna; Calışkan, Yahya Kemal; Erdem, Olgun; Canbak, Tolga (Journal of Coloproctology, 2025)
Chronic anal fissure is a common condition affecting all ages. Surgical intervention is often necessary for severe cases. Recent studies indicate that the success of surgical procedures for chronic anal fissures is closely linked to the patient's bowel movements. Constipation can impede healing and increase the risk of complications post-surgery. This article investigates the correlation between pre-surgery constipation and the efficacy of fissure surgery, while also examining its impact on treatment outcomes.We conducted a retrospective cohort study. Patients who underwent surgery for chronic anal fissures were evaluated for age, complaints, anorectal examination characteristics, and anatomical localization of fissures. The Rome IV criteria were used to diagnose functional constipation associated with anal fissures. We investigated the relationship between pre-surgery constipation and treatment success.Baseline constipation was detected in 21.4% of patients. At the 6-month follow-up, 28 patients failed to fully recover, but baseline constipation did not affect treatment success (p = 0.306). Additionally, Among the 28 patients with pre-surgery constipation, 15 still experienced constipation, while 8 of the 103 patients without pre-surgery constipation developed constipation postoperatively.Our study found that the success of fissure surgery treatment was not affected by constipation. These results suggest that the theory of constipation and hard stool may be inadequate to fully explain the causes and success of surgical treatment for anal fissures. Other theories, such as high basal internal sphincter pressure and related ischemia, should be considered.
Keywords: chronic anal fissure; treatment success; surgery; constipation; lateral internal sphincterotomy